2017
DOI: 10.3389/fpsyg.2017.00840
|View full text |Cite
|
Sign up to set email alerts
|

Personality Styles of German-Speaking Psychotherapists Differ from a Norm, and Male Psychotherapists Differ from Their Female Colleagues

Abstract: Variables pertaining to the person of the psychotherapist have been neglected in psychotherapy research for some time. Concerning personality in particular, however, research has mostly focused on its relation with the psychotherapist’s choice of method, or differences between the various major therapy approaches. That is, psychotherapists were compared to each other without specifying how exactly psychotherapists are in comparison to “ordinary people.” We wanted to know: Are there specific personality styles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…The data of our 2015 survey (Peter et al, 2017) indicated that the personality styles of N = 1,027 psychotherapists from the three German speaking countries Germany, Austria and Switzerland (DACH countries) differed from the norm (i.e., T-scores of 50 in Figure 1). In 2015 we had divided the personality styles into three groups according to the effect sizes of the differences.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…The data of our 2015 survey (Peter et al, 2017) indicated that the personality styles of N = 1,027 psychotherapists from the three German speaking countries Germany, Austria and Switzerland (DACH countries) differed from the norm (i.e., T-scores of 50 in Figure 1). In 2015 we had divided the personality styles into three groups according to the effect sizes of the differences.…”
Section: Discussionmentioning
confidence: 89%
“…The mean T-scores of the personality styles of these two groups are depicted in Table 5. They as well as the means of the combined group of the N = 430 can also be seen as personality profiles in Figure 2 together with that of the reference group of the N = 1,027 DACH psychotherapists of 2015 (Peter et al, 2017). When comparing personality styles of securely attached (n = 342) to those of insecurely attached (n = 88) psychological psychotherapists, significant differences were found for the willful/paranoid (PN), spontaneous/borderline (BN), and reserved/schizoid (SZ) styles, as well as for the loyal/ dependent (AB), self-critical/negativistic (NA), unselfish/selfsacrificing (SL), self-critical/avoidant (SU), passive/depressive (DE), and optimistic/rhapsodic (RH) styles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations